Synthesis, Characterization and Antimicrobial Evaluation of New Schiff Bases Containing 4-Hydroxycoumarin - Karrar A. Hchim; kamel, Mohammed (Iraqi Journal of Pharmaceutical Sciences, 2025)
The goal of This study is to make new coumarin derivatives, describe them in detail from a chemical standpoint, and test their antimicrobial properties. New Schiff base of compound (III) 2-[(2-oxo-2H-chromen-4-yl)oxy]acetohydrazide have been successfully prepared by the reaction of proper aryl/hetero aromatic aldehydes with compound (III) under conventional Conditions.The compound 4-hydroxycoumarin (I) undergoes a reaction with ethylbromoacetate in the presence of potassium carbonate and dry acetone, resulting in the formation of comound )II( ethyl2-((2-oxo-2h-chromen-4-yl)oxy)acetate , which subsequently, in the presence of ethanol, interacted with hydrazine hydrate to create compound (III) 2-[(2-oxo-2H-chromen-4-yl)oxy]acetohydrazide . The Antimicrobial activity of the recently synthesized Coumarin derivatives was evaluated against a range of microorganisms, including 2 Gram negative bacteria (Escherichia coli & Pseudomonas aeruginosa), 2 Gram positive bacteria (Streptococcus pneumoniae & Staphylococcus aureus), and the Candida albicans fungus. In this current investigation, new coumarin derivatives were prepared and afterwards subjected to characterization using ATR-FTIR Spectroscopy and (1HNMR) spectroscopy. The initial investigation into the antimicrobial properties of the last synthetic compounds revealed that compounds IVa, IVb, IVc ,IVd exhibited varying degrees of antibacterial and antifungal activity.